Radiometric parameters of the sacrum and pelvis in patients with dysfunctions of the sacroiliac joint, affecting the spinae-pelvic balance in the frontal plane - Staude, Volodymyr; Radzishevska, Yevgenya; Zlatnyk, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to study the radiographic parameters of the sacrum and pelvis in patients with dysfunction of the sacroiliac joint, which affects the spinal-pelvic balance in the frontal plane and their interrelation. Methods: 50 patients aged 20 to 71 years with sacroiliac joint dysfunction were included in the survey. Standing X-rays were analyzed: 1) the angle of sacral cranial plate inclinationby the method of R. E. Irvin; 2) pelvic tilt angle; 3) angle of rotation of the sacrumthe axial axis by the method of O. M. Orla; 4) the width of the articular clefts of the sacroiliac joint in the ventral, medial and dorsal parts. Indicators were calculated statistically. Results: in 25 patients (50 %) deviations in all positions were found to be less than 3°, in 6 (12 %) — more than 3°, in 5 (10 %) — the maximum inclination of the sacrum. Most of the subjects (90 %) had an asymmetry of the width of the articular clefts of the sacroiliac joint, which averaged (3.5 ± 1.1) mm. The subjects are divided into 4 clusters: I — with a high degree of asymmetry of the width of the articular surfaces in the ventral section, negligible in the medial and dorsal, with a large inclination of the sacrum and pelvis, with a large rotation of the sacrum; ІІ — with practically symmetrical width of articular surfaces in all threears, inclination of the pelvis and sacrum, a large rotation of the spacecraft; III — with a significant asymmetry of the width of the articular cracks in the medial section and small in the dorsal, large inclination of the pelvis and sacrum, with a large rotation of the sacrum; IV — with a large asymmetry of the width of articular surfaces in the dorsal part and minimal in the ventral and medial parts, small inclination of the sacrum and pelvis, with a small rotation of the sacrum. Conclusions: in the majority of patients (90 %), the asymmetry of the width of the articular surfaces of the sacroiliac joint was revealed, in the rest — pelvic inclination, inclination and rotation of the sacrum. The inclination of the sacrum was recorded in 78 % of patients, the pelvis — 84 %, the rotation of the sacrum — in 92 %. An unfavorable prognosis was found in patients with I, III and IV clusters — 60 % of all surveyed.